Advanced remote focus control in multicore meta-fibers through 3D nanoprinted phase-only holograms - Mohammadhossein Khosravi; Torsten Wieduwilt; Matthias Zeisberger; Adrian Lorenz; Markus A. Schmidt (Nature Communications)
Abstract In this study, we present an unexplored approach for remote focus manipulation using 3D nanoprinted holograms integrated on the end face of multi-core single-mode fibers. This innovative method enables precise focus control within a monolithic metafiber device by allowing light coupled into any of the 37 cores to be precisely focused at predefined locations. Our approach demonstrates significant advances over conventional lenses and offers unique functionalities through computationally designed holograms. This research marks the first successful use of multi-core fibers for remote focus control via 3D nanoprinting, achieving crosstalk-free operation at visible wavelengths. Key findings include strong agreement between design, simulation, and experimental results, highlighting the potential of this technology to improve applications in fields such as biological optics, laser micromachining, telecommunications, and laser surgery. This work opens new avenues for the development of advanced optical systems with superior focus control capabilities.